Elucidating the Excited‐State Properties of CuInS2 Nanocrystals upon Phase Transformation: Quasi‐Quantum Dots Versus Bulk Behavior. (26th February 2015) - Azimi, Hamed; Kuhri, Susanne; Stahl, Melissa S.; Hou, Yi; Guldi, Dirk M.; Brabec, Christoph J.
<x xml:space="preserve">Abstract</x> New insights into the complex relation between the thermal phase transformation and the excited state properties of chalcopyrite CuInS2 nanocrystals (CIS NCs) are presented. An in situ solution processing method via depositing molecular precursors is applied, offering advantages in terms of simplicity, low‐temperature processability, and control over crystallite size, and optical properties. At low annealing temperatures, strong carrier quantum confinement and small crystallite sizes are realized for CIS NC films. CIS crystal growth is found to set in at higher annealing temperatures inducing a complete transformation from quasi‐quantum‐dot (QD) via bulk‐like to bulk behavior. The transition of a near‐infrared localized surface plasmon resonance (LSPR) towards a bulk‐like plasmon resonance documents the crystal growth and further acts as a valuable probe to relate crystallite size with copper‐deficient stoichiometries. In addition, time‐resolved photophysical investigations help to shed light on the dynamics and mechanisms of exciton and charge carrier generation of CIS NC films as a function of annealing temperature. The in situ‐prepared CIS NC films are further passivated by a thin CdS layer, leading to the formation of long‐lived excitons and an effective CIS ground‐state depletion.